The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5772/intechopen.99030
|View full text |Cite
|
Sign up to set email alerts
|

Phytobiotics, a Natural Growth Promoter for Poultry

Abstract: Genetic advance aimed at accelerating the growth rate of slaughter birds have reduced the natural resistance of poultry to infections. It also increased susceptibility to stress, which resulted in deterioration of the welfare and productivity of poultry. Additionally, intensive poultry production poses a risk of exposure of chickens to unfavorable zoo-hygienic conditions and contamination with pathogens from the external environment (bedding, water, feed, hen house staff, sick birds in the flock). Due to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…This was probably due to the low digestibility of the fiber component of leaves. The decrease in feed intake could be explained by the impaired palatability due to the existence of a higher amount of saponins when DULM was supplemented above 5% [18]. On the contrary, Lu et al [19] observed an increase in feed intake in layers when 5% Moringa leaf was used in the diet whereas Das et al [20] reported that the Indian runner hens' intake was not affected by DULM in their diet.…”
Section: Discussionmentioning
confidence: 99%
“…This was probably due to the low digestibility of the fiber component of leaves. The decrease in feed intake could be explained by the impaired palatability due to the existence of a higher amount of saponins when DULM was supplemented above 5% [18]. On the contrary, Lu et al [19] observed an increase in feed intake in layers when 5% Moringa leaf was used in the diet whereas Das et al [20] reported that the Indian runner hens' intake was not affected by DULM in their diet.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Mahfuz and Piao [ 17 ] stated that higher breast muscle weight could be assigned to the increased protein deposition in birds fed diets supplemented with Moringa. Considered as one of the most important benefits of MOM to chicken feeding in our study, this improvement in breast weight could also be the result of the high content of phytobiotics from Moringa, since Krauze [ 57 ] indicated that phytobiotics may increase the weight of the pectoral muscle in chickens. Finally, this higher breast weight could be associated with the fiber diameter of this muscle, as Rehman et al [ 58 ] stated that Moringa increased breast muscle fiber diameter.…”
Section: Discussionmentioning
confidence: 77%
“…These products have been used as natural growth promoters in pigs and poultry [ 19 , 20 , 22 , 25 ]. Plant extracts (oregano, laurel, sage, anise, and citrus essential oils) have a positive effect on slaughter performance and the health of broiler chickens [ 26 , 27 ]. Some herbs and spices, including turmeric, cumin, black, and red peppers, nutmeg, mint, ginger, as well as chamomile or anise, also have immunostimulating properties [ 19 ].…”
Section: Immunomodulatory Properties Of Bioactive Productsmentioning
confidence: 99%